Estudio de factibilidad para la creación de una empresa dedicada a la confección de lencería hospitalaria en la zona Eloy Alfaro del Distrito Metropolitano de Quito - Arteaga Guamán, Nathalie Alejandra (2012)
Because of the importance of asepsis in different institutions dedicated to health, different pathologies including; nosocomial infections, influenzas, epidemics, etc. Nursing homes have seen the need to constantly renew and purchase lingerie hospital. With the creation of a company engaged in the manufacture and marketing of household and hospital linen seeks to address this need in the community.